HIPOKALEMIK PERIODIK PARALISIS - Anik Widjajanti; S.M. Agustini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
A 7-year-old boy of Java origin, visited the doctor with progressive weakness everytime he ate food containing Monosodium Glutamat (MSG). Progressive weakness began from his legs and spreaded to the arms as well (sometimes also to the neck). He could neither walk nor do anything for 5–6 hours then began to resolve spontaneously.. We suspected the diagnosis of hypokalaemic periodic paralysis upon the history of episodes of flacid paralysis and low serum concentration of potassium (< 3,5 mmol/L) during the attacts. The clinical examination showed that this boy is in good general and nutritional conditions; electrocardiogram, laboratory blood count, urinalisis, thyroid, liver, kidney function, and ANA test were normal as well. The family history of flacid paralysis was negative. We have promptly administered potassium orally and his condition was improved progressively including less degree of flacid paralysis (the weakness). A genetic testing, electromyography (EMG), muscle biopsy and another examination has not performed.